Critical Thinking and Reflective Learning in the Marketing Education Literature: A Historical Perspective and Future Research Needs. (August 2018) - Dahl, Andrew J.; Peltier, James W.; Schibrowsky, John A.
Marketing educators have long espoused the importance of critical thinking as a means of developing students' higher-order problem-solving skills. In this article, we utilize an historical approach to investigate how educators have defined, operationalized, and empirically evaluated the critical thinking construct. To accomplish this, we review the critical thinking literature from three prominent marketing education journals and the leading management education journal. In doing so, we summarize extant critical thinking research across varied pedagogical topics, review empirical findings, and present a conceptual framework for motivating future research.